1996
DOI: 10.1080/17450399609381892
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the influence of dietary fibre sources with different proportions of soluble and insoluble fibre on Ca, Mg, Fe, Zn, Mn and Cu apparent absorption in rats

Abstract: The 6 week experiment was performed on growing Wistar male rats. In the third and the sixth weeks digestibility trials were performed. The following high fibre preparations were supplemented to the control diet (C): high methoxylated citrus pectin (Cr); apple pomace (A), potato fiber "Povex" (P) and sugar beet pulp (B). Fibre supplementation, except Cr, significantly increased Ca, Mg, Fe, Mn, Zn, Cu excretion in faeces and decreased their apparent absorption in both trials. Significant correlations (P < or = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 9 publications
0
18
2
Order By: Relevance
“…An important feature of potato fibre found in the present study is its positive effect on the digestibility of mineral components as compared with cellulose, the respective apparent digestibility coefficients of ash being 51.0 vs. 41.4%. This result differs from that found by Gralak et al (1996), who found negative effects of PF on absorption of single minerals in rats. However, the greater absorption of mineral matter by rats fed on PF in our experiment was confirmed by the significantly higher final ash content in the body (2.64 vs. 2.17% of BW, respectively).…”
Section: Biochemical Parameterscontrasting
confidence: 86%
See 1 more Smart Citation
“…An important feature of potato fibre found in the present study is its positive effect on the digestibility of mineral components as compared with cellulose, the respective apparent digestibility coefficients of ash being 51.0 vs. 41.4%. This result differs from that found by Gralak et al (1996), who found negative effects of PF on absorption of single minerals in rats. However, the greater absorption of mineral matter by rats fed on PF in our experiment was confirmed by the significantly higher final ash content in the body (2.64 vs. 2.17% of BW, respectively).…”
Section: Biochemical Parameterscontrasting
confidence: 86%
“…In rats, PF added to a low-fibre diet depressed digestibility of protein and fat but not of energy (Antuszewicz 2006). However, negative effects of PF on absorption of particular minerals in rats (Gralak et al 1996) and on energy digestibility in pigs (Jørgensen 1998) were also found.…”
Section: Introductionmentioning
confidence: 90%
“…A well‐known substance with detrimental effects on Ca absorption is for example phytic acid which is present in all seeds and which is substantially enriched in the by‐products of seed processing such as grain bran or oil‐seed extracts. Also dietary fibre may influence Ca absorption (G arlak et al 1996; H ara et al 1996). An excessive protein intake is considered to reduce the intermediate Ca utilization due to calciuria (P annemans et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This was seen as reduction of intestinal villi and hyperplasia within crypts, leading to impaired absorption in the intestine. Previous studies have shown that administration of lectins to animals per os leads to pancreatic hypertrophy and degenerative changes in organs such as kidney and liver [35, 36, 37]. The negative impact was not seen in the presence of raw soy phytates, which reduce the absorption of phosphorus by forming complexes with it.…”
Section: Resultsmentioning
confidence: 95%